Influence of Menstrual Cycle Phases on Physical Performance and Injury Risk: A Narrative Review - Hofman, Julia; Kowalczyk, Aleksandra; Staniszewska, Wiktoria; Pączek, Adrian Jan; Dyczek, Paweł (Journal of Education, Health and Sport, 2025)
Background. The growing professionalisation of women’s sport necessitates a deeper understanding of female-specific physiology. The influence of the menstrual cycle (MC) and hormonal contraceptives (HC) on performance and health is a critical area of research, though historically hindered by significant methodological limitations. Objective. This narrative review aims to synthesize contemporary evidence (2021–2025) regarding the influence of the menstrual cycle and hormonal contraceptive use on physical performance metrics and musculoskeletal injury risk in female athletes. Methods. A structured narrative review of 25 key publications (including systematic reviews, meta-analyses, and pivotal original trials) sourced from major scientific databases was conducted. The synthesis focused on identifying the current consensus on performance modulation, injury susceptibility, methodological standards, and holistic athlete management. Results. The synthesis reveals a clear divergence: while the direct impact of MC phase on maximal strength and aerobic capacity appears minimal or trivial for most athletes, the influence on musculoskeletal injury risk is clinically significant. Evidence confirms a heightened risk of injury during the late follicular and ovulatory phases, linked to altered neuromuscular control. Furthermore, hormonal contraceptives do not appear to offer protection against musculoskeletal injuries. The review highlights that subjective symptoms are often more detrimental to training availability than the physiological phase itself. Conclusions. The findings challenge the utility of rigid, phase-based training periodization for performance enhancement. Future efforts must prioritize two key areas: (1) improved methodological rigor in research, specifically the biochemical verification of cycle phases, and (2) the implementation of individualized, education-led monitoring systems that focus on managing subjective symptoms and athlete well-being.